EMPOWERMENT OF PKK ORIENTED READY-TO-USE PRODUCTS TOWARDS INDEPENDENT BUSINESS GROUP IN BOYOLANGU SUB-DISTRICT, BANYUWANGI REGENCY: PEMBERDAYAAN PKK BERORIENTASI PRODUK SIAP PAKAI MENUJU KELOMPOK USAHA MANDIRI DI KELURAHAN BOYOLANGU KABUPATEN BANYUWANGI - Harwanti Noviandari (MAN Insan Cendekia Jambi, 2020)
The emergence of used goods business has an impact on the impression of a slum that appears in Boyolangu Village, making Boyolangu village a pandemic area for dengue fever. To change this condition, approaches are needed that must be carried out, one of which is strengthening the PKK organization while the problems faced by the PKK are 1. The sewing skills carried out by the sub-district government are not sustainable. 2. Problems with very vulnerable families 3. Not familiar with business management and marketing strategies 4. Provision of production tools for business sustainability. From the problems faced by partners in Boyolangu Village who are urban residents who do not have the skills for independent businesses because there are no tools to develop businesses to increase economic income during a pandemic. The provision of sewing training becomes knowledge to become a ready-to-use production business. Forming a somasy group which is a training and mentoring approach that is given to partners to increase knowledge in solving family and environmental problems. Optimization of management and marketing is an effort to improve the economy of partners in Boyolangu Village. Solutions to problems can be provided based on the results of problem identification that become a reference in preparation, implementation, monitoring, evaluation and reporting. Boyolangu Village is growing with the emergence of ready-made businesses and the existence of a product marketing area. So that the Boyolangu village has a new identity as an independent village, which is a competitive advantage and bargaining power for ready-to-use products that are sought after by local and foreign consumers.